Guideline on current good radiopharmacy practice (cGRPP) for the small-scale preparation of radiopharmaceuticals - Nic Gillings; Olaug Hjelstuen; Jim Ballinger; Martin Behe; Clemens Decristoforo; Philip Elsinga; Valentina Ferrari; Petra Kolenc Peitl; Jacek Koziorowski; Peter Laverman; Thomas L. Mindt; Oliver Neels; et al. (SpringerOpen, 2021)
Abstract This guideline on current good radiopharmacy practice (cGRPP) for small-scale preparation of radiopharmaceuticals represents the view of the Radiopharmacy Committee of the European Association of Nuclear Medicine (EANM). The guideline is laid out in the format of the EU Good Manufacturing Practice (GMP) guidelines as defined in EudraLex volume 4. It is intended for non-commercial sites such as hospital radiopharmacies, nuclear medicine departments, research PET centres and in general any healthcare establishments. In the first section, general aspects which are applicable to all levels of operations are discussed. The second section discusses the preparation of small-scale radiopharmaceuticals (SSRP) using licensed generators and kits. Finally, the third section goes into the more complex preparation of SSRP from non-licensed starting materials, often requiring a purification step and sterile filtration. The intention is that the guideline will assist radiopharmacies in the preparation of diagnostic and therapeutic SSRP's safe for human administration.